(untitled) (Medico Legal Update, 2021)
The aim of this study was to investigate the effect of Prolonged Overdose Sorbitol and Aspartame Administration on serum Lipid Profile levels in female Rats. Blood samples were obtained from (18) adult female rats that treated with (100 mg/day) of sorbitol and (18) rats that treated with of Aspartame for 30 days, as well as (18) healthy rats that were given (Normal Saline) for 30 days as a control group. They divided into three groups as the following: Sor Group:- Included eighteen female rats that treated with (100 g/day) of sorbitol, Asp Group:- Included eighteen female rats that treated with (100 g/day) of Aspartame control Group:- Included (18) healthy rats that was given (Normal Saline) for 30 days. Results: the results in this study showed no significantly different (p?0.05) in (TC), (TG), (HDL), (LDL), (VLDL) levels in the treated group with Asp in comparison with control group while serum (TG) and (vLDL) showed significant increase (p?0.05) in treated group with Sor in comparison with control group, also the study reveals significant increase (p?0.05) in serum (TG) and (vLDL) in treated group with Sor in comparison with treated group with Asp while there were no significant different (p?0.05) in serum (TC), (HDL), levels in the group that treated with Sor in comparison with group treated with Asp and control group. In conclusion: The use of overdoses than permissible of sorbitol and aspartame for a prolonged period leads to disturbance of lipid profile levels, but it is statistically imperceptible.